2016
DOI: 10.1007/s41105-016-0086-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of restless legs syndrome among Japanese pregnant women without gestational complications

Abstract: To determine the prevalence of restless legs syndrome (RLS) among Japanese pregnant women without complications, and to clarify the correlation between RLS and clinical outcomes, RLS screening was conducted using the Johns Hopkins Telephone Diagnostic Interview for 140 pregnant women in their third trimester. The frequency of positive RLS screening test was 15.7%. No significant differences were found in the hemoglobin, ferritin, and folate levels and in the delivery outcomes between the RLS and control groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
(14 reference statements)
0
4
3
Order By: Relevance
“…However, no other pregnancyrelated complication was observed. While there are some reports of an association between RLS/WED and gestational complications [11,32] as well as delivery outcomes [11,14], other studies did not observe an association between RLS/WED and delivery outcomes [15,31,32]. Although we cannot assume an association between maternal sleep/wake problems and the stillbirth in this case observed here, further studies are needed to clarify the influence of RLS/WED on delivery outcomes.…”
Section: Sleep Disordered Breathing Among Pregnant Womencontrasting
confidence: 64%
See 2 more Smart Citations
“…However, no other pregnancyrelated complication was observed. While there are some reports of an association between RLS/WED and gestational complications [11,32] as well as delivery outcomes [11,14], other studies did not observe an association between RLS/WED and delivery outcomes [15,31,32]. Although we cannot assume an association between maternal sleep/wake problems and the stillbirth in this case observed here, further studies are needed to clarify the influence of RLS/WED on delivery outcomes.…”
Section: Sleep Disordered Breathing Among Pregnant Womencontrasting
confidence: 64%
“…However, the presence of RLS/WED did not affect EDS, insomnia symptoms, or subjective sleep quality. In pregnant Japanese women without gestational complications, few severe cases of RLS/WED have been reported, and almost all RLS/WED patients reported only mild to moderate symptoms [15]. Among 8 patients suspected with RLS/WED during the third trimester of pregnancy in this study, 7 reported moderate to severe symptoms.…”
Section: Sleep Disordered Breathing Among Pregnant Womenmentioning
confidence: 58%
See 1 more Smart Citation
“…However, no other pregnancy-related complication was observed. While there are some reports of an association between RLS/WED and gestational complications [11,32] as well as delivery outcomes [11,14], other studies did not observe an association between RLS/WED and delivery outcomes [15,31,32]. Although we cannot assume an association between maternal sleep/wake problems and the stillbirth in this case observed here, further studies are needed to clarify the influence of RLS/WED on delivery outcomes.…”
Section: Restless Legs Syndrome/willis-ekbom Disease Among Pregnant Wcontrasting
confidence: 64%
“…Also, these maternal sleep/wake problems affect cesarean delivery, preterm birth rates, rates of children born small-and large-for-gestational-age, and admission rates to the neonatal intensive care unit [6,8,[11][12][13][14]. However, findings are inconsistent, and discrepancies among studies are thought to be influenced by methodological differences across studies [6,8,12,13,15]. Also, mutual interactions among different types of sleep/wake problems cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%